Marcin Mielczewski and Music under the Patronage of the Polish Vasas Translated by John Comber - Przybyszewska-Jarminska, Barbara; Przybyszewska-Jarminska, Barbara (Peter Lang, 2014)
The first monograph of the life and œuvre of Marcin Mielczewski (d. 1651) presents the best known Polish composer of seventeenth-century Europe. During the 1990s, while exploring a newly accessible collection of music manuscripts from Silesia (the Sammlung Bohn) held in the Berlin Staatsbibliothek, the author found 37 compositions signed M.M., which she ascribed to Mielczewski. This discovery, representing more than half the composer s known legacy, fuelled a considerable rise in interest in Mielczewski s output among musicologists and musicians. In this book, the current state of knowledge about Marcin Mielczewski s life and work is presented within the context of the musical patronage of King Ladislaus IV Vasa of Poland and his brother, Bishop Charles Ferdinand.